Analysis of typical applications of geophysical well logs in geological fields - Jin LAI; Yang SU; Chengwen XIAO; Yidi ZHAO; Bo ZHU; Youpeng ZHANG; Xiaojiao PANG; Guiwen WANG (地质科技通报)
Objective To better interpret the geological information contained in geophysical logging data and expand the application scope of well logs in geology, Methods several typical cases of representative logging data are analyzed. This analysis seeks to enhance the use of well logs in geological research. Logging data can aid in the deployment of sidetracking wells by identifying tectonic occurrences and variations in their combination characteristics. Image log data also enable determintion of palaeocurrent directions and the identification of bidirectional provenance supply, thus providing refined and scientifically calibrated interpretations in alignment with geological understanding. Results Logging data, often regarded as the "eyes" of geologists, are advantageous for identifying and evaluating pores, caves, fractures, and other subsurface features. These data are crucial for discovering hydrocarbon reservoirs and facilitating the fine and continuous calculation of reserve parameters. The coupling relationships between mudstone resistivity, acoustic interval transit time, and in situ stress in logging curves can also be used to indirectly predict the quality of ultradeep reservoirs and hydrocarbon productivity. Moreover, combining geology, logging, and seismic activity allows for the delineation of hydrocarbon traps and supports oil and gas exploration and production. Conclusion The analysis of these typical cases assists geologists in better interpreting the geological information in logging curves and further broadens the application field and scope of geophysical logging data.